China : new engine of world growth - Garnaut, Ross; Song, Ligang (ANU E Press, 2012)
Twenty-five years of reform have transformed China from a centrally planned and closed system to a predominantly market-driven and open economy. As a consequence, China is emerging as the new powerhouse for the world economy. China: new engine for world growth discusses the impact and significance of this transformation. It points out risks to the growth process and unfinished tasks of reform. It presents conclusions from recent research on growth, trade and investment, the financial sector, income and regional disparities, industrial location and private sector development. Ross Garnaut is a Professor of Economics in the Research School of Pacific and Asian Studies, and Chairman of the China Economy and Business Program at The Australian National University. He was Australia's Ambassador to China in the 1980s. Ligang Song is a Fellow in the Asia Pacific School of Economics and Government, and Director of the China Economy and Business Program at The Australian National University.